MEMBANGUN DEMOKRASI BERKUALITAS MELALUI PENGAWASAN PARTISIPATIF PADA PILKADA SERENTAK 2024 - Fitra Mulyawan; Zennis Helen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Participatory oversight is a crucial element in building a quality democracy, especially in the 2024 simultaneous regional elections. This article examines the role of participatory oversight in ensuring transparency, accountability, and integrity in the electoral process. The method used is descriptive qualitative analysis with a literature study approach and secondary data from previous election monitoring reports. The article finds that community participation in election monitoring can prevent violations, increase public trust and strengthen the legitimacy of election results. Recommendations include community capacity building, socialization of participatory monitoring, and collaboration between election administrators and civil society.Keywords: Democracy, Participatory Supervision, Simultaneous Regional Elections 2024, Transparency, Accountability